Habitat overlap and interspecific competition between snow leopards and leopards in the Central Himalayas of Nepal - Narayan Prasad Koju; Paul Buzzard; Arati Shrestha; Shailendra Sharma; Kai He; Juan Li; Randall C. Kyes; Cheng Chen; William V. Beisch (Global Ecology and Conservation, 2024)
Traditionally, leopards (Panthera pardus) and snow leopards (P. uncia) occupy distinct habitats. This study explored the coexistence of snow leopards and leopards within the Gaurishankar Conservation Area in Lapchi Valley, Nepal. Both leopard species are crucial for ecosystem stability as apex predators. Camera trapping data from 2018 to 2023 confirmed twenty species of wild mammals and two species of domesticated livestock in Lapchi Valley, where snow leopards have strong spatio-temporal overlap (Δ=0.74) with leopards. Snow leopards exhibited distinct temporal patterns before and after the leopards’ arrival in the study area. Generalized Linear Mixed Effect Models (GLMM) revealed seasonal and prey-type associations with leopard presence, highlighting the snow leopards' preference for cold season and wild prey. Leopards, however, did not show a significant seasonal preference. The findings highlight Lapchi Valley's ecological richness as well as the need for comprehensive conservation strategies. The record of spatial and temporal overlap between the leopards and snow leopards provides important insights into the behavioral dynamics of apex predators and the need for targeted biodiversity conservation in the face of changing ecosystems. The study emphasizes the valley's transboundary significance, calling for collaborative efforts between Nepal and China to help promote effective conservation management. Lapchi Valley's isolation, traditional and religious importance, and recent infrastructure developments further impact the conservation challenges.